HUBUNGAN KUALITAS PELAYANAN TERHADAP KUNJUNGAN ULANG PASIEN RAWAT JALAN DI POLI PENYAKIT DALAM RSUD H. ABDUL MANAP KOTA JAMBI - Azkia, Meira Putri; Sitepu, Fransiska; Samsinar (Journal of Hospital Administration and Management (JHAM), 2025)
Quality health services are a major determinant of patient satisfaction and loyalty, including their decision to return to treatment. This study aims to determine the extent of the influence of service quality on the intention to revisit outpatients at the Internal Medicine Poly at RSUD H. Abdul Manap Jambi City. The study was conducted using a quantitative approach and cross-sectional design, involving 99 respondents who were selected incidentally. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed that three of the five dimensions of service quality had a significant relationship with the intention to revisit, namely (responsiveness) with a p value of 0.027, (assurance) with a p value of 0.000, and (empathy) with a p value of 0.003. While dimension (tangible) with a p value = 0.271 and (reliability) with a p value = 0.234 did not show a significant relationship. This finding confirms that the responsiveness of staff, the sense of security provided, and personal attention are very important in shaping patient loyalty. Therefore, improving the quality of service in these aspects needs to be a priority for the hospital in